Clinical features and prognosis of nocardiosis in patients with connective tissue diseases. Issue 3 (4th May 2021) - Yagishita, Mizuki; Tsuboi, Hiroto; Tabuchi, Daiki; Sugita, Toshiki; Nishiyama, Taihei; Okamoto, Shota; Terasaki, Toshihiko; Shimizu, Masaru; Honda, Fumika; Ohyama, Ayako; Kurata, Izumi; Abe, Saori; et al.
Abstract: Objectives: To investigate the clinical features and prognosis of nocardiosis complicated by connective tissue diseases (CTDs). Methods: We examined patients with CTDs who were diagnosed with nocardiosis from October 2004 to 2019. We retrospectively investigated patient characteristics and therapeutic outcomes. We then performed a comparison between survivors and non-survivors. Results: Fourteen patients were examined. Underlying CTDs were systemic lupus erythematosus (28.6%), vasculitis syndrome (28.6%), rheumatoid arthritis (21.4%), adult Still disease (14.3%) and dermatomyositis (7.1%). Infected organs were lung (85.7%), brain (42.9%), skin/cutaneous lesions (28.6%) and muscle (7.1%). Disseminated infections were seen in nine patients (64.3%). At the onset of nocardiosis, all patients were given prednisolone (23.2 ± 11.9 mg/day). Only two patients (14.3%) were given TMP-SMX for prophylaxis of pneumocystis pneumonia. Relapse occurred in one patient (7.1%) and four patients (28.6%) died from nocardiosis for a cumulative survival rate at 52 weeks of 76.9%. In a comparison of survivors (71.4%) and non-survivors (28.6%), cutaneous lesions were significantly more frequent in the latter (10 vs 75%, p  = .04) with an odds ratio of 27.0 (95% CI: 1.7–453.4). Conclusion: Cutaneous lesions as a result of dissemination might be a risk factor for nocardiosis mortality in patients with CTDs.